Conflicts over the Condition and Management of Green Spaces and Their Possible Solutions - Eiselt, Gábor Károly (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
Green spaces play a crucial role in ensuring ecological sustainability, urban liveability, and public well-being. However, increasing urbanisation, land-use pressures, and conflicting stakeholder interests have led to a rise in disputes over the condition, use, and planning of these areas. This study explores the most common types of conflicts related to urban green spaces, including tensions between conservation goals and development plans, accessibility concerns, and differing community expectations. Drawing on case studies from Central and Eastern Europe, the paper analyses the root causes of such conflicts and categorises them by actor involvement, spatial scale, and legal framework. The second part of the study focuses on conflict resolution mechanisms. The findings underline the importance of transparent governance, inclusive dialogue, and adaptive planning in mitigating conflicts and promoting the sustainable management of green areas.